Microstructure and Composition of Red Mud-Fly Ash-Based Geopolymers Incorporating Carbide Slag - Shi, Yuxuan; Zhang, Zhaoyun; Sang, Zhaohu; Zhao, Qingxin (Frontiers in Materials, 2020)
In order to solve the problem of the recycling utilization about an industry waste solid-red mud, a kind of geopolymer material system based on red mud-fly ash-carbide slag has been developed. The microstructure and composition of the geopolymer material system at the age of 28 days was tested by the scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD). It was showed that the compressive strength of the geopolymer sample was 15.1 MPa when the liquid solid ratio (L/S) was 0.7, sand-binder ratio was 3:1, alkaline activator used carbide slag, and the fly ash, red mud and carbide slag were prepared as the proportion of 4:3:3. Through SEM-EDS and XRD results, the spherical beads in fly ash were dissolved in the alkaline environment to form silicon and aluminum monomers. Carbide slag played the roles of calcium component support in C-A-S-H, C-S-H gels and alkaline activator.